Urban and Regional Planning in São Paulo, Brazil in the 60"s. - Silva Leme, Maria Cristina (International Planning History Society Proceedings, 2016)
In the 1960s, a combination of new political, social and economic processes led to a change in urban and regional planning in Brazil. On the one hand, the economic planning that had been introduced in an incipient manner into the federal government’s agenda since the end of the Vargas Era acquired greater importance and played a growing role both in sectorial and public spheres. On the other hand, increased and more complex team building both in public bodies and in private engineering and architecture offices was a response both to a new territoriality in the urbanization process and to an increase in demands created by this new government agenda. In the 1950s, offices such as Hidroservice (founded in 1958) and Hidrobrasileira (founded in 1954) developed projects for water supply works, hydroelectric power plants and the opening of highways. Although these offices initially focused on engineering works, throughout the 1960s they formed increasingly complex teams that included professionals specialized in economic planning and urban and regional planning. Sociedade para Análise Gráfica e Mecanográfica de Complexos Sociais (SAGMACS) which was created at the end of the 1940s by professionals, politicians and intellectuals linked to French priest Louis Joseph Lebret, conducted research in São Paulo and in other Brazilian states. Some of the professionals that comprised SAGMACS’ research teams were called to work for the Plano de Ação do Governo do Estado (PAGE) de São Paulo (the São Paulo State action plan).After the end of Plano de Ação, some of the technicians who had worked for it returned to SAGMACS, while others founded ASPLAN and Planasa, a consultancy on public administration affairs. ASPLAN, an office created at the beginning of 1963, developed several studies and plans for cities in the interior of São Paulo State and for the capital’s metropolitan region, as well as for other Brazilian states. The present study analyzes the formation and the modus operandi of the urban and regional planning offices and teams in the 1960s, especially in São Paulo. The professional and political trajectories of the technicians who comprised the teams in these offices reveals the different concepts and trends in urbanism adopted in the various Plans drawn up for different government spheres. We have based our analysis on the hypothesis that the two processes complement each other and also explain a planning crisis in the period and the signs of subsequent transformation. The military coup of 1964 had a big impact on political, academic and intellectual structures, as it interrupted processes and dismantled institutions. At the same time, this period saw a rupture in political structures, the exclusion of certain groups and the expulsion of technicians and intellectuals, who were subsequently forbidden from working and remaining in the country. This process also saw the maintenance of existing political and technical actions and the emergence of resistance actions, which would subsequently cause tension in the system. In this research, we analyze the complexity of these relations through their tensions, ruptures and continuity.